Religious Policy of the Mamluk Sultan Baybars (1260–1277 AC) - Mahamid, Hatim Muhammad (Religions, 2023)
This study focuses on the religious policy of the Mamluk Sultan Rukn al-Din Baybars (d. 1277), and its application throughout his rule in Egypt and Syria (Bilād al-Shām). This study also discusses the impact of this policy and its benefit for Muslims and Islam in general in the region. Dealing with the character of Baybars of Mamluk origin is very important in this study to obtain the required answers to the questions related to the Islamic character of Mamluk rule in the regions of the Middle East in the Middle Ages. Although Baybars’ background was as a slave (mamlūk), who was not familiar with the religion of Islam, he had to prove his ability to act as a leader of an Islamic state. Baybars worked to implement the principles of Islam according to the Quran and the tradition of the Prophet (sunna), thus exploiting his status as an Islamic leader and as Sultan during his reign. Baybars was strict in his religious policy toward those who committed forbidden acts according to the Islamic religion, and he was keen to punish them and implement the Sharīʿa as required, in cooperation with the ʿulamā. Baybars was given relevant degrees and titles he deserved by the revived Abbasid Caliph in Cairo, such as a “holy warrior” (Mujāhid), “partner of emir of believers/the Caliph” (Qasīm Amīr al-Mu’minīn), and other religious titles that testify his high-ranking religious status as defender of Islam.